Axiology and Anomaly in the Practice of Mixed Methods Work: Pragmatism, Valuation, and the Transformative Paradigm. (October 2015) - Biddle, Catharine; Schafft, Kai A.
This article uses a Kuhnian framework to explain the adoption of the transformative paradigm in pragmatically informed mixed methods research. We argue that pragmatism represents a model of "normal science" among many mixed methods researchers and that Kuhn's concept of the scientific anomaly provides an instructive metaphor for understanding what we interpret to be a failure of pragmatic mixed methods researchers to adequately account for the axiological foundation for their work. The transformative paradigm thus can be read as providing pragmatic researchers with an axiological "fix" that sidesteps the larger question of how to establish a philosophically consistent means of specifying research value. We discuss this argument in light of pragmatist philosophy, the recent history of mixed methods research, and the future development of the field.